Mobilising the Masses Populist Conservative Movements in Australia and New Zealand During the Great Depression - Cunningham, Matthew (ANU Press, 2022)
The radical right has gained considerable ground in the twenty-first century. From Brexit to Bolsonaro and Tea Partiers to Trump, many of these diverse manifestations of right-wing populism share a desire to co‑opt or supplant the mainstream parties that have traditionally held sway over the centre right. It is now more important than ever to understand similar moments in Australian and New Zealand history. This book concerns one such moment-the Great Depression-and the explosion of large, populist conservative groups that accompanied the crisis. These 'citizens' movements', as they described themselves, sprang into being virtually overnight and amassed a combined membership in the hundreds of thousands. They staunchly opposed party politicians and political parties for their supposed inaction and infighting. Whether left or right, it did not matter. They wanted to use their vast numbers to pressure their governments into enacting proposals they believed were in the national interest: a smaller, more streamlined government where Members of Parliament were free to act according to their conscience rather than their party allegiance. At the same time, the movements prescribed antidotes for their nations' economic ill‑health that were often radical and occasionally anti-democratic. At the height of their power, they threatened to disrupt or outright replace the centre right political parties of the time-particularly in Australia. At a time when fascism and right-wing authoritarianism were on the march internationally, the future shape of conservative politics was at stake.